Ensuring Operational Reliability of Overpass on "Almaty-Kapshagai" Highway Section in Kazakhstan - Assylkhan Jalairov; Dauren Kumar; Khaini-Kamal Kassymkanova; Gulshat Murzalina; Gulnar Jangulova (Communications - Scientific letters of the University of Zilina, 2022)
The article presents results of the overpass condition survey, technical survey, static tests and assessment of the structure operational reliability, a doubledecker overpass on Almaty-Kapshagai highway section in Kazakhstan. Technical survey determined the dimensions of the overpass, the camber of reinforced concrete superstructures main beams and checked the values of the overpass roadway actual transverse and longitudinal slopes. The calculation and analytical assessment of the overpass load-bearing structures, for the strength of the bending moment, are performed. Static tests of the overpass split beam superstructure of a length of 33.0m were conducted. Trucks loaded with ballast were accepted as a test load.